Intensive Polyoma Virus Nephropathy Treatment as a Preferable Approach for Graft Surveillance - Dheir, H.; Sahin, S.; Uyar, M.; Gurkan, A.; Turunc, V.; Kacar, S.; Bayirli Turan, D.; Basdemir, G. (Transplantation proceedings, 2011)
Polyoma BK virus nephropathy (BKVN) is one of the important causes of graft failure and loss among renal transplant patients. Reduction of immunosuppression is the most important preferred treatment approach; however, there is no agreed protocol for additional treatments. Our aim was to investigate the effects on graft survival of intensive treatment protocols for BKVN among renaltransplant patients. 214 patients were included in the study. All patients underwent investigation for the presence of BKV in plasma samples every 3 months starting from the third month after transplantation. Biopsies were obtained upon detection of graft dysfunction or viremia. If BKVN was positive, viremia was investigated monthly. Plasma plus biopsy-proven BKVN were detected in 19 patients (8.9%), whose mean age was 45.8 ± 12.0 years; 68.4% (n = 13) were male and 94.7% (n = 18) were recipients of a living-donor kidney. There were 5.2% (n = 1) diabetic subjects, and the mean time prior to dialysis was 39.6 ± 44.8 (3–125) months. BKVN was observed at a mean of 6.8 ± 2.9 (4–14) months after the transplantation. It positively correlated with the baseline serum creatinine level ( r = 0.159; P = .02), application and cumulative dose of antithymocyte globulin ( r = 0.177; r = 0.165; respectively; P = .01), mean tacrolimus dose ( r = 0.303; P < .001), and hepatitis B virus positivity ( r = 0.169; P = .01). Immunosuppression was decreased in all patients who developed BKVN. In addition, leflunomide was applied in 68%, intravenous immunoglobulin in 74%, and cidofovir in 32% of patients. Acute rejection rates did not increase significantly after lowering immunosuppression ( P > .05). BKVN is one of the important problems in renal transplant patients. Intensive treatment of BKVN with heterogeneous regimens, including combined treatment with leflunamide + IVIG together with immunosuppressive dose reduction, was an effective approach to prolong graft survival.